An Analysis of Distractive Behavior and Learning Barriers in Fifth-Grade Students at SD 1 Ngemplak - Mufidatul Inayah (Al Hikmah: Journal of Education, 2025)
Distractive behavior and learning disabilities are common problems among fifth-grade elementary school students and have the potential to disrupt the effectiveness of the learning process. This study aims to describe the characteristics of students' distractive behavior, analyze the factors causing learning disabilities, and examine the reciprocal relationship between academic disabilities and distractive behavior in fifth-grade students at SD 1 Ngemplak. The study used a qualitative approach with a case study design. Subjects were purposively selected: fifth-grade students exhibiting distractive behavior accompanied by learning disabilities, with supporting informants including classroom teachers and school officials. Data collection techniques included classroom observation, semi-structured interviews, and document analysis of student learning outcomes. Data analysis was conducted through the stages of data reduction, categorization, and interpretation, using triangulation of sources and methods to ensure data validity. The results showed that distractive behavior in students varied in intensity and was closely correlated with basic academic abilities, particularly reading and writing. High-intensity distractive behavior was found in slow-learners who had not yet mastered basic literacy, while in other students, distractive behavior was situational and manageable. These findings indicate that distractive behavior is not simply a behavioral problem, but rather a manifestation of learning barriers that lead to academic frustration and poor self-regulation. This research emphasizes the importance of an inclusive, differentiated learning approach, and collaboration between teachers, schools, and parents in addressing learning barriers and distractive behavior comprehensively and sustainably.